2018
DOI: 10.2196/humanfactors.9569
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Facing Diabetes Dashboard Embedded in a Patient Web Portal: Design Sprint and Usability Testing

Abstract: BackgroundHealth apps and Web-based interventions designed for patients with diabetes offer novel and scalable approaches to engage patients and improve outcomes. However, careful attention to the design and usability of these apps and Web-based interventions is essential to reduce the barriers to engagement and maximize use.ObjectiveThe aim of this study was to apply design sprint methodology paired with mixed-methods, task-based usability testing to design and evaluate an innovative, patient-facing diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…A prior study recommended using real-life patient stories that demonstrate how a patient portal can be used to make the case for why a patient portal might be valuable [ 54 ]. There also remains a need to do more usability testing with patient portals and apply user-centered design approaches to better understand what features within the patient portal would be valuable to patients [ 55 - 57 ]. Studies have identified a number of usability issues, including not having information presented in multiple languages, lack of educational resources, poor data visualization and lack of contextualization for laboratory values, and lack of personalization [ 58 - 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study recommended using real-life patient stories that demonstrate how a patient portal can be used to make the case for why a patient portal might be valuable [ 54 ]. There also remains a need to do more usability testing with patient portals and apply user-centered design approaches to better understand what features within the patient portal would be valuable to patients [ 55 - 57 ]. Studies have identified a number of usability issues, including not having information presented in multiple languages, lack of educational resources, poor data visualization and lack of contextualization for laboratory values, and lack of personalization [ 58 - 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified a number of usability issues, including not having information presented in multiple languages, lack of educational resources, poor data visualization and lack of contextualization for laboratory values, and lack of personalization [ 58 - 60 ]. In response, some systems have tested creative strategies, such as offering tailored patient education, and have used motivational strategies (eg, social comparisons and gamification) to enhance the relevance of the patient portal and ensure that the portal is meeting user needs [ 55 , 61 ]. Future studies are needed to test strategies that align the patient portal with patients’ information needs.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, when communicating test results via portals, it is necessary to include information about the test itself (eg, test capability, the purpose of test), easy-to-understand explanations of medical jargon, the results in the context of the patient’s health, directions for next steps, and specific educational resources [ 35 , 50 , 51 ]. Furthermore, designers and developers of patient portals should embody user-centered approaches to significantly improve the design of patient portals to present information in a more meaningful way [ 29 , 52 ]. Finally, national test result notification and interface design standards for patient portals should be developed to ensure interoperability and consistency in features across portal vendors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are also published on the role of human factors engineering in designing usable health IT for patients, such as a diabetes dashboard embedded in a patient portal 37 , an app for geriatric heart failure self-care 38 , and an app for medication management 39 . The domain of consumer health IT has embraced human factors and usability methods 40 .…”
Section: Human-centered Design Of Health Itmentioning
confidence: 99%